2003
DOI: 10.1073/pnas.0836984100
|View full text |Cite
|
Sign up to set email alerts
|

New components of the honey bee ( Apis mellifera L.) queen retinue pheromone

Abstract: The honey bee queen produces pheromones that function in both releaser and primer roles such as attracting a retinue of workers around her, attracting drones on mating flights, preventing workers from reproducing at the individual (worker egg-laying) and colony (swarming) level, and regulating several other aspects of colony functioning. The queen mandibular pheromone (QMP), consisting of five synergistic components, is the only pheromone chemically identified in the honey bee (Apis mellifera L.) queen, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
162
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(166 citation statements)
references
References 30 publications
0
162
0
4
Order By: Relevance
“…In those insect societies that are headed by a single once-mated queen, the degree of asymmetry might be higher than in those with multiple queens. In the single-queen systems, the degree of asymmetry may approach the critical point, leading queens to use pheromones to manipulate workers [40,41], which leads to more prevalent worker policing in these species [37]. The experimental results of the model developed here may help explain the different strategies of different insect societies.…”
Section: Figurementioning
confidence: 94%
“…In those insect societies that are headed by a single once-mated queen, the degree of asymmetry might be higher than in those with multiple queens. In the single-queen systems, the degree of asymmetry may approach the critical point, leading queens to use pheromones to manipulate workers [40,41], which leads to more prevalent worker policing in these species [37]. The experimental results of the model developed here may help explain the different strategies of different insect societies.…”
Section: Figurementioning
confidence: 94%
“…The queen's anatomy is characterized by an enlarged ovary (180−200 ovarioles per ovary) and a sperm-storage organ, the spermatheca, that can store over 5 million spermatozoa (Kraus et al, 2004;Snodgrass, 1956). The end stylet of the queen's stinging apparatus is smooth so it can be retracted after stinging, and the queen produces a specific signature of C21-C33 cuticular hydrocarbons in addition to a pheromone blend from enlarged glands in the head (mandibular gland), abdomen (Dufour and tergite gland), and tarsus (tarsal gland); major components being (E)-9-oxodec-2-enoic acid, (E)-9-hydroxydec-2-enoic acid, methyl phydroxybenzoate, and 4-hydroxy-3-methoxyphenylethanol (Free, 1987;Keeling et al, 2003).…”
Section: A Anatomy Of Individualsmentioning
confidence: 99%
“…These five compounds act together to maintain reproductive dominance and elicit worker retinue behaviour. Keeling et al (2003) identified four other components that are not of mandibular gland origin, namely methyl (Z )-octadec-9-2-en-1-o l (methyl oleate), (E )-3-(4-hydroxy-3-methoxyphenyl)-prop-2-en-1-o l (coniferyl alcohol), hexadecane-1-o l and (Z9 , Z12 , Z15 )-octadeca-9, 12, 15-trienoic acid (linolenic acid), which act in synergy with QMPs to elicit retinue behaviour. This leads to a terminology shift from QMP to queen retinue pheromones (QRP) (Slessor et al, 2005).…”
Section: Introductionmentioning
confidence: 99%